E2F-7 couples DNA damage-dependent transcription with the DNA repair process. - Zalmas, L; Coutts, A; Helleday, T; La Thangue, N (Taylor and Francis, 2013)
The cellular response to DNA damage, mediated by the DNA repair process, is essential in maintaining the integrity and stability of the genome. E2F-7 is an atypical member of the E2F family with a role in negatively regulating transcription and cell cycle progression under DNA damage. Surprisingly, we found that E2F-7 makes a transcription-independent contribution to the DNA repair process, which involves E2F-7 locating to and binding damaged DNA. Further, E2F-7 recruits CtBP and HDAC to the damaged DNA, altering the local chromatin environment of the DNA lesion. Importantly, the E2F-7 gene is a target for somatic mutation in human cancer and tumor-derived mutant alleles encode proteins with compromised transcription and DNA repair properties. Our results establish that E2F-7 participates in 2 closely linked processes, allowing it to directly couple the expression of genes involved in the DNA damage response with the DNA repair machinery, which has relevance in human malignancy.